2020
DOI: 10.4103/jpbs.jpbs_104_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial efficacy of calcium hydroxide along with proton pump inhibitor against Enterococcus faecalis

Abstract: A BSTRACT Aim: The aim of this study was to evaluate in vitro the efficacy of pantoprazole, a proton pump inhibitor, alone, and in combination with calcium hydroxide against Enterococcus faecalis , a star survivor in endodontic pathology. Materials and Methods: Teeth were inoculated with E. faecalis strains MTCC 439 and were divided into groups. Group 1 used salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…However, the gel form of the mixture did not show anti-bio lm potential and the colony count in 24 h proved the low anti-bio lm ability of these two mixtures. Namitha et al declared that PP-CH is more effective than CH alone which con rms our results (31). Anija et al reported concentrationdependent effect of lansoprazole as another PPI on CH against E. faecalis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the gel form of the mixture did not show anti-bio lm potential and the colony count in 24 h proved the low anti-bio lm ability of these two mixtures. Namitha et al declared that PP-CH is more effective than CH alone which con rms our results (31). Anija et al reported concentrationdependent effect of lansoprazole as another PPI on CH against E. faecalis.…”
Section: Discussionsupporting
confidence: 88%
“…Screening the colonies of E.faecalis revealed that PP-nZnO has antibacterial effect like NaOCl in 24h. Since there was no evidence on antibacterial abilities of PP-nZnO, these positive results may be explained by inhibiting proton pumps by PP, which destructs optimal cytoplasmic pH levels of the bacteria (31). The mixture of CH-nZnO in powder form showed synergic effect on suppressing bio lm formation of E.faecalis.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, Enterococcus faecalis exhibits resilience towards elevated pH levels, enabling it to thrive in the presence of calcium hydroxide (Ca(OH) 2 ) commonly employed during root canal treatment ( Elashiry et al, 2023 ). This adaptability can be attributed to the utilization of a proton pump by Enterococcus faecalis within their plasma membrane, facilitating effective regulation of cytoplasmic equilibrium and endurance against high alkalinity ( Divakar et al., 2020 ). Therefore, in the presence of this bacterium within an infected root canal, utmost efforts should be made to eliminate it.…”
Section: Introductionmentioning
confidence: 99%
“…E. faecalis, a gram-positive and facultatively anaerobic bacterium, is difficult to remove from the root canal due to its ability to invade areas that are difficult to access with mechanical instruments. It can also form biofilms that make it more resistant to antimicrobial agents and grow in environments that lack nutrients [11][12][13][14]. Furthermore, E. faecalis is resistant to alkaline pH, essentially due to the presence of proton pumps that lower the pH in such conditions [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It can also form biofilms that make it more resistant to antimicrobial agents and grow in environments that lack nutrients [11][12][13][14]. Furthermore, E. faecalis is resistant to alkaline pH, essentially due to the presence of proton pumps that lower the pH in such conditions [11][12][13][14]. C. albicans is a dimorphic fungus (switching from yeast to hypha) and is the most common isolate of persistent endodontic infections.…”
Section: Introductionmentioning
confidence: 99%